Low-energy-consumption high-strength inorganic insulation board and preparation method thereof

By using raw materials such as iron tailings, feldspar powder and alkali exciter solutions for room temperature foaming, low-energy consumption and high-strength inorganic insulation boards were prepared, which solved the problems of compressive strength and preparation cost of existing inorganic insulation boards, and realized the Excellent flame retardant, thermal insulation performance and low energy consumption preparation.

CN119241152APending Publication Date: 2025-01-03HEFEI UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411408164.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing inorganic insulation boards have shortcomings in compressive strength and preparation cost, and the traditional process consumes high energy and is complicated in the preparation process.

Method used

Iron tailings, feldspar powder, water glass, hydrogen peroxide, cationic surfactant cetyl trimethyl ammonium bromide and thickener sodium carboxymethyl cellulose as raw materials, and the alkali exciter solution and room temperature foaming technology Prepare inorganic porous geological polymers without high temperature calcination, forming inorganic insulation boards with low energy consumption and high strength.

Benefits of technology

It realizes excellent flame retardant, thermal insulation performance and high compressive strength of inorganic insulation boards, while reducing preparation energy consumption and cost. Its performance complies with the Type I standard of "JG/T 435-2014".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241152A_ABST
    Figure CN119241152A_ABST
Patent Text Reader

Abstract

The invention discloses a low-energy-consumption high-strength inorganic insulation board and a preparation method thereof. The low-energy-consumption high-strength inorganic insulation board is prepared from the following raw material components in parts by mass: 18-30 parts of iron tailings, 0-12 parts of feldspar powder, 25-35 parts of water glass, 1-2 parts of hydrogen peroxide, 0.1-0.2 part of a cationic surface active agent hexadecyl trimethyl ammonium bromide and 0.05-0.15 part of a thickening agent sodium carboxymethyl cellulose. The prepared inorganic insulation board not only has excellent flame retardance and heat insulation performance, but also has low ecological toxicity, and the dry density, the compressive strength, the volume water absorption rate and other performance of the inorganic insulation board meet the JG / T435-2014 I type standard requirements. The preparation method disclosed by the invention is simple in process and free of high-temperature calcination, so that the preparation energy consumption is greatly reduced, the iron tailings and the feldspar powder in the used raw materials belong to bulk solid wastes, the raw material cost is reduced to a certain extent, the preparation method belongs to a low-energy-consumption preparation process, the preparation cost is reduced, and the preparation method has certain economic benefit value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal insulation materials, and particularly relates to a low-energy-consumption and high-strength inorganic thermal insulation board and a preparation method thereof. Background Art

[0002] Traditional exterior wall insulation boards are mainly organic insulation boards such as EPS boards, XPS boards, and rigid foam polyurethane. Although organic insulation boards have the advantages of low cost and small weight, they have a series of problems such as low flame retardancy, poor thermal insulation, low compressive strength, and strong eco-toxicity, which has greatly reduced the scale of application of organic insulation boards in the construction industry. Compared with the above-mentioned traditional organic insulation boards, insulation boards with inorganic materials rich in silicon and aluminum such as expanded perlite as the main raw materials not only have excellent flame retardancy and thermal insulation properties, but also have the advantage of low eco-toxicity. This type of inorganic insulation board has become a research hotspot in the exterior wall insulation material industry among wall insulation materials and has been gradually promoted and applied. However, because the raw material of this type of inorganic insulation board is expanded perlite, the processing and production process of expanded perlite is relatively complicated. It is necessary to pre-treat the mineral rock and then perform preheating and expansion operations. It is a typical high-cost raw material. In addition, the foaming process of expanded perlite inorganic insulation board belongs to the traditional room temperature foaming mode. The single pore structure formed during the foaming process is not conducive to the strength development of inorganic insulation board. .

[0003] In recent years, there have been many reports on inorganic insulation boards. For example, Chinese patent CN114934602A discloses a method for preparing an inorganic composite insulation board with low thermal conductivity, high thermal insulation and high fire resistance. However, the preparation process is complicated, the sample has a high moisture content, and the compressive strength is low, which can only reach ≥0.2MPa. Chinese patent CN111763062A discloses an inorganic fiber insulation board and a preparation method thereof. The raw materials selected are metallurgical slag and coal gangue, but the raw material utilization rate is low, and the preparation environment requirements are high, and the energy consumption cost is high. Chinese patent CN103011879B discloses an inorganic foamed cement insulation board and a preparation method thereof, which has good thermal insulation effect and is light in weight. However, its production cost is high, and the compressive strength is low, only reaching ≥0.45MPa. Chinese patent CN105399439A discloses an inorganic foam insulation board with low thermal conductivity and low density and a preparation method thereof. However, its compressive strength is not high overall, and the preparation environment requirements are strict. Chinese patent CN115557759A discloses a low-density inorganic composite Class A non-combustible insulation board and its preparation method. However, its compressive strength is too low, only ≥0.10MPa. Chinese patent CN101638918A discloses a preparation process for iron tailings sintered porous insulation board, the process is: shale and iron tailings are crushed and ground, and the fineness of the grinding is 20-80μm after screening and metering; the ground shale and iron tailings are added with toughening agent, solvent and foaming agent in proportion and mixed, and water is added to form balls and granules. After natural drying, the raw material balls are distributed in the mold, and then put into the kiln for firing. The firing process is carried out in a segmented insulation manner, and finally the cooled board is demolded and the finished product is stacked; but this preparation method needs to be fired at high temperature, which has high energy consumption.

[0004] Therefore, there is an urgent need to find an inorganic insulation board with low energy consumption, low production cost and high compressive strength and a preparation method thereof. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a low-energy-consumption and high-strength inorganic thermal insulation board and a preparation method thereof.

[0006] In order to achieve the above technical objectives, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a low-energy consumption and high-strength inorganic insulation board, comprising the following raw material components in parts by weight: 18 to 30 parts of iron tailings, 0 to 12 parts of feldspar powder, 25 to 35 parts of water glass, 1 to 2 parts of hydrogen peroxide, 0.1 to 0.2 parts of cationic surfactant hexadecyltrimethylammonium bromide, and 0.05 to 0.15 parts of thickener sodium carboxymethyl cellulose.

[0008] Preferably, the raw material components include the following parts by mass: 18 to 30 parts of iron tailings, 0 to 12 parts of feldspar powder, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of cationic surfactant hexadecyltrimethylammonium bromide, and 0.09 parts of thickener sodium carboxymethyl cellulose.

[0009] Preferably, the median particle size of the iron tailings is less than 75 μm; and the particle size of the feldspar powder is 100-200 meshes.

[0010] The second aspect of the present invention provides a method for preparing the above-mentioned low-energy consumption and high-strength inorganic thermal insulation board, comprising the following steps:

[0011] S1, mixing and stirring liquid silicate, hexadecyltrimethylammonium bromide and sodium carboxymethyl cellulose to obtain an alkaline activator solution;

[0012] S2, according to the formula, the iron tailings and feldspar powder are mixed evenly, and then added to the alkaline activator solution, and stirred to mix evenly to obtain a solid-liquid mixture;

[0013] S3, adding hydrogen peroxide to the solid-liquid mixture, stirring and mixing evenly to obtain a geopolymer solid-liquid mixture;

[0014] S4, placing the obtained geopolymer solid-liquid mixture into a mold and foaming it to obtain a porous geopolymer;

[0015] S5. Perform thermal activation to accelerate the geological polymerization reaction, demould, and obtain a low-energy consumption and high-strength inorganic insulation board.

[0016] Preferably, in step S1, the mass ratio of water glass, cationic surfactant hexadecyltrimethylammonium bromide and sodium carboxymethyl cellulose is 30:0.18:0.09.

[0017] Preferably, in step S1, the stirring and mixing time is 5 to 15 minutes, and the stirring speed is 700 to 1000 r / min.

[0018] Preferably, in step S2, the stirring and mixing time is 8 to 20 minutes; and the stirring speed is 500 to 700 r / min.

[0019] Preferably, in step S3, the mixing and stirring time is 1 to 10 min; and the stirring speed is 500 to 700 r / min.

[0020] Preferably, in step S4, the foaming is carried out at room temperature for 15 to 30 hours.

[0021] Preferably, in step S5, the thermal activation time is 18 to 30 hours.

[0022] The present invention has the following beneficial effects:

[0023] (1) The present invention selects iron tailings and feldspar powder as raw materials to provide components of SiO2 and Al2O3 geopolymer skeletons, and forms a silicate-based polymer with an amorphous three-dimensional network structure through a geopolymerization reaction under the action of an alkali activator. The polymer has stable physical and chemical properties, good durability, strong impermeability, and the like. In the present invention, the foaming agent hydrogen peroxide is used to spontaneously decompose into O2 and H2O at room temperature, and the decomposition rate is accelerated in an alkaline environment. In the present invention, the raw materials are prepared to form inorganic porous geopolymers (inorganic insulation boards) without sintering by using alkali excitation + hydrogen peroxide room temperature foaming technology, so that the inorganic insulation board has a higher strength under a lower bulk density, and then the foam stabilizer cationic surfactant hexadecyltrimethylammonium bromide is used to modify the slurry, so that the foaming effect is better, the pore distribution in the inorganic porous geopolymer is more uniform, and the total porosity is greatly improved. In the present invention, the use of a thickener, sodium carboxymethyl cellulose, is beneficial to increasing the viscosity of the slurry, improving the strength of the inorganic thermal insulation board, reducing the formation of through holes, and reducing the thermal conductivity of the inorganic thermal insulation board, thereby enhancing its thermal insulation performance; through the synergistic effect of the above-mentioned components, the inorganic thermal insulation board finally prepared not only has excellent flame retardancy, thermal insulation performance and compressive strength, but also has the advantage of low eco-toxicity, and its dry density, volume water absorption rate and other properties also meet the requirements of Type I standard of "JG / T 435-2014".

[0024] (2) The preparation method of the present invention has a simple process and does not require high-temperature calcination, thereby greatly reducing the energy consumption of preparation.

[0025] (3) The inorganic thermal insulation board prepared by the present invention uses iron tailings and feldspar powder as raw materials, which are large-scale solid wastes. This reduces the cost of raw materials to a certain extent. In addition, the production process does not need to be carried out under high temperature and high pressure, and is a low-energy consumption production process, which reduces the production cost. Therefore, it has certain economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 A synthesis route map of a low-energy consumption and high-strength inorganic thermal insulation board provided by the present invention;

[0028] Figure 2 XRD patterns of iron tailings, feldspar powder and the inorganic thermal insulation board prepared in Example 4;

[0029] Figure 3 This is the particle size distribution diagram of iron tailings. DETAILED DESCRIPTION

[0030] In the following description, specific details such as specific system structures, technologies, etc. are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present invention.

[0031] Example 1

[0032] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 30 parts of iron tailings, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of hexadecyl trimethyl ammonium bromide, 0.09 parts of sodium carboxymethyl cellulose, see Figure 1 , and its preparation steps are as follows:

[0033] S1. Weigh water glass and hexadecyltrimethylammonium bromide according to the ratio, set the speed to 1000 r / min, mix and stir evenly for 5 minutes, then add sodium carboxymethyl cellulose, set the speed to 1000 r / min, mix and stir evenly for 2 minutes to obtain an alkaline activator solution;

[0034] S2. Weigh the iron tailings and feldspar powder according to the formula, crush them after drying, and pass them through a 200-mesh sieve. Then, mix the two evenly and put them into the alkaline excitation solution. Set the speed to 600 r / min, mix and stir evenly for 10 minutes to obtain a uniform and stable solid-liquid mixture.

[0035] S3, adding hydrogen peroxide to the solid-liquid mixture, setting the rotation speed to 600r / min, uniformly mixing and stirring for 1min, to obtain a geopolymer solid-liquid mixture to be foamed;

[0036] S4, placing the obtained geopolymer solid-liquid mixture into a mold, covering it and foaming it at room temperature for 24 hours to obtain a porous geopolymer;

[0037] S5. Perform 24h thermal activation to accelerate the geological polymerization reaction. After the reaction is completed, demoulding is performed to obtain a low-energy consumption and high-strength inorganic insulation board.

[0038] Example 2

[0039] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 27 parts of iron tailings, 3 parts of feldspar powder, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of hexadecyltrimethylammonium bromide, and 0.09 parts of sodium carboxymethyl cellulose. The preparation steps are the same as those in Example 1.

[0040] Example 3

[0041] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 24 parts of iron tailings, 6 parts of feldspar powder, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of hexadecyltrimethylammonium bromide, and 0.09 parts of sodium carboxymethyl cellulose. The preparation steps are the same as those in Example 1.

[0042] Example 4

[0043] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 21 parts of iron tailings, 9 parts of feldspar powder, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of hexadecyltrimethylammonium bromide, and 0.09 parts of sodium carboxymethyl cellulose. The preparation steps are the same as those in Example 1.

[0044] Example 5

[0045] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 18 parts of iron tailings, 12 parts of feldspar powder, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of hexadecyltrimethylammonium bromide, and 0.09 parts of sodium carboxymethyl cellulose. The preparation steps are the same as those in Example 1.

[0046] Example 6

[0047] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 24 parts of iron tailings, 6 parts of feldspar powder, 25 parts of water glass, 2.5 parts of hydrogen peroxide, 0.18 parts of hexadecyltrimethylammonium bromide, and 0.09 parts of sodium carboxymethyl cellulose. The preparation steps are the same as those in Example 1.

[0048] Example 7

[0049] A low-energy consumption and high-strength inorganic insulation board is composed of the following components in parts by weight: 24 parts of iron tailings, 6 parts of feldspar powder, 25 parts of water glass, 2.5 parts of hydrogen peroxide, 0.1 parts of hexadecyltrimethylammonium bromide, and 0.07 parts of sodium carboxymethyl cellulose. The preparation steps are the same as those in Example 1.

[0050] The inorganic thermal insulation board test blocks prepared in Examples 1-7 were subjected to the following tests: the dry density test method was in accordance with GB / T5486-2008; the compressive strength test method was in accordance with GB / T5486-2008; the volume water absorption test method was in accordance with GB / T5486-2008; and the thermal conductivity test method was in accordance with GB / T 10294-2008. The results are shown in Table 1.

[0051] Table 1

[0052]

[0053] From the results in Table 1, it can be seen that the raw materials in Example 1 are all iron tailings. Compared with Examples 2-5, it can be observed that adding a certain amount of feldspar powder can promote the geopolymerization reaction, retain more bubbles inside the geopolymer slurry in the early slurry foaming stage, and ultimately reduce the dry density of the inorganic insulation board. At the same time, the compressive strength of the inorganic insulation board can be improved.

[0054] It can be observed from the results of Examples 1-5 that the overall dry density shows a trend of first decreasing and then increasing, and the overall change is not obvious. However, under the raw material components of Example 4, the compressive strength has been significantly improved. This is because under the action of the same component of the foaming agent hydrogen peroxide, the foaming effect of the early insulation board is the same, and the Si-O bond formed during the alkali excitation of the geopolymer is much higher than the Al-O bond. When the Si content in the raw material is high, more energy will be required to destroy the chemical bond when the depolymerization and polycondensation reaction occurs, causing the geopolymerization reaction to be slow; when the Si content is less, it will affect the formation of the geopolymer network structure, so the raw material silicon-aluminum ratio is too high or too low. It will have an adverse effect on the alkali excitation effect. Therefore, by adjusting the ratio of iron tailings and feldspar powder in the raw material, the optimal alkali-excited raw material silicon-aluminum ratio can be found, so that the geopolymerization reaction is accelerated, the strength of the insulation board is improved, and the dry density of the insulation board is reduced at the same time.

[0055] It can be observed from the results of Examples 6-7 that the reduction in the amount of water glass will have an adverse effect on the performance of the inorganic insulation board. This is because the alkali activator content is reduced, the alkali excitation reaction is gradually reduced, and the material strength is reduced. In the early stage of foaming, the slurry strength cannot support more pores, and collapse is prone to occur, reducing the performance of the insulation board. The reduction in the amount of hexadecyltrimethylammonium bromide and sodium carboxymethylcellulose also has a significant impact on the various properties of the inorganic insulation board. By modifying the water glass alkali activator by adding the surfactant hexadecyltrimethylammonium bromide and the thickener sodium carboxymethylcellulose, the bubbles can be evenly dispersed in the slurry to form a uniform porous structure. At the same time, the incorporation of the thickener sodium carboxymethylcellulose can also increase the modulus of the interfacial film, thereby enhancing the foam stability by preventing the bubbles from merging.

[0056] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. A low energy consumption and high strength inorganic insulation board, characterized in that: The invention comprises the following raw material components in parts by weight: 18 to 30 parts of iron tailings, 0 to 12 parts of feldspar powder, 25 to 35 parts of water glass, 1 to 2 parts of hydrogen peroxide, 0.1 to 0.2 parts of cationic surfactant hexadecyltrimethylammonium bromide, and 0.05 to 0.15 parts of thickener sodium carboxymethyl cellulose.

2. A low energy consumption and high strength inorganic thermal insulation board according to claim 1, characterized in that: The invention comprises the following raw material components in parts by weight: 18 to 30 parts of iron tailings, 0 to 12 parts of feldspar powder, 30 parts of water glass, 1.8 parts of hydrogen peroxide, 0.18 parts of cationic surfactant hexadecyltrimethylammonium bromide, and 0.09 parts of thickener sodium carboxymethyl cellulose.

3. A low energy consumption and high strength inorganic thermal insulation board according to claim 1 or 2, characterized in that: The median particle size of the iron tailings is less than 75 μm; the particle size of the feldspar powder is 100 to 200 μm.

4. A method for preparing a low-energy consumption and high-strength inorganic thermal insulation board as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1. Mix and stir liquid silicate, hexadecyltrimethylammonium bromide and sodium carboxymethyl cellulose according to a formula to obtain an alkaline activator solution; S2, according to the formula, the iron tailings and feldspar powder are mixed evenly, and then added to the alkaline activator solution, and stirred to mix evenly to obtain a solid-liquid mixture; S3, adding hydrogen peroxide to the solid-liquid mixture, stirring and mixing evenly to obtain a geopolymer solid-liquid mixture; S4, placing the obtained geopolymer solid-liquid mixture into a mold and foaming it to obtain a porous geopolymer; S5. Perform thermal activation to accelerate the geological polymerization reaction, demould, and obtain a low-energy consumption and high-strength inorganic insulation board.

5. The method for preparing a low-energy-consumption and high-strength inorganic thermal insulation board according to claim 1, characterized in that: In step S1, the mass ratio of water glass, cationic surfactant hexadecyltrimethylammonium bromide and sodium carboxymethyl cellulose is 30:0.18:0.09; the stirring and mixing time is 5 to 15 minutes, and the stirring speed is 800 to 1500 r / min.

6. The method for preparing a low-energy-consumption and high-strength inorganic thermal insulation board according to claim 1, characterized in that: In step S2, the mixing and stirring time is 8 to 20 minutes; the stirring speed is 500 to 900 r / min.

7. The method for preparing a low-energy-consumption and high-strength inorganic thermal insulation board according to claim 1, characterized in that: In step S3, the stirring and mixing time is 1 to 10 minutes; the stirring speed is 500 to 900 r / min.

8. The method for preparing a low-energy-consumption and high-strength inorganic thermal insulation board according to claim 1, characterized in that: In step S4, the foaming is carried out at room temperature for 15 to 30 hours.

9. The method for preparing a low-energy-consumption and high-strength inorganic thermal insulation board according to claim 1, characterized in that: In step S5, the thermal activation time is 18 to 30 hours.

Citation Information

Patent Citations

  • Iron tailings based geopolymer porous material and preparation method thereof

    CN109574558A

  • Foam heat insulation board prepared from iron tailings and preparation method thereof

    CN110256045A

  • Thermal insulation material prepared from obsidian and preparation method thereof

    CN111792879A

  • Geopolymer material containing iron tailing powder and granite stone powder and preparation method of geopolymer material

    CN113773001A

  • New method for preparing wall thermal insulation material from building solid waste

    CN118666560A